Discussions; [Drag on vertical sill of forced jump effort de trainée sur un seuil vertical soumis a un ressaut force] - Ohtsu I.; Yasuda Y.; Yamanaka Y.; Karki K.S.; Kumar S. (My University, 2025)
[No abstract available]